2003
DOI: 10.1038/sj.onc.1206880
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer-specific gene 1 interacts with the mitotic checkpoint kinase BubR1

Abstract: The abnormal expression of breast cancer-specific gene 1 (BCSG1) in malignant mammary epithelial cells is highly associated with the development and progression of breast cancer. A series of in vitro and in vivo studies performed in our laboratory and others have demonstrated that BCSG1 expression significantly stimulates proliferation, invasion, and metastasis of breast cancer cells. However, currently little is known about how BCSG1 exerts its oncogenic functions. To elucidate the cellular mechanisms underly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
104
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 96 publications
(109 citation statements)
references
References 30 publications
4
104
1
Order By: Relevance
“…Studies have shown that disruption of BubR1 activity results in a loss of checkpoint control, chromosomal instability, and/or early onset of malignancy (41). Previous studies using yeast two-hybrid screening revealed an interaction of SNCG with BubR1 (30). Because SNCG compromises SAC function and renders a resistance to antimicrotubule drug, we reason that SNCG-BubR1 interaction may contribute to the inhibition of SAC as a result of nonmutational inactivation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies have shown that disruption of BubR1 activity results in a loss of checkpoint control, chromosomal instability, and/or early onset of malignancy (41). Previous studies using yeast two-hybrid screening revealed an interaction of SNCG with BubR1 (30). Because SNCG compromises SAC function and renders a resistance to antimicrotubule drug, we reason that SNCG-BubR1 interaction may contribute to the inhibition of SAC as a result of nonmutational inactivation.…”
Section: Discussionmentioning
confidence: 99%
“…The C-terminal kinase domain is involved in the phosphorylation of critical components of a mitotic checkpoint, whereas N-terminal is involved in interaction with SAC component Cdc20. Previous studies conducted through yeast two-hybrid screening revealed an interaction of SNCG with BubR1 (30). To gain more insight into their interacting mechanism and to determine whether such interaction will cause the structural changes of BubR1, a docking analysis was carried out to understand the interaction between SNCG and the crystallographic structure of human BubR1.…”
Section: Molecular Modeling Of Interaction Between Sncg and Bubr1mentioning
confidence: 99%
See 2 more Smart Citations
“…Likewise, Bub3 haploinsufficiency promotes aneuploidy, and Bub3þ/À mice develop tumors rapidly in response to carcinogen [Babu et al, 2003]. In addition, SAC inactivation may play a role in the development of leukemia and breast cancer because the TAX oncoprotein encoded by the human T cell leukemia virus binds and inhibits Mad1p [Jin et al, 1998], and expression of the oncogenic Breast Cancer Specific Gene 1 (BCSG-1) reduces BubR1p abundance [Gupta et al, 2003].…”
Section: The Sac and Cancermentioning
confidence: 99%